The Female Voice in Low budget, independent cinema of Australia: Strange Colours, The Second & Hot Mess. Issue 3 (2nd September 2021) - Hart, Phoebe; Leder, Marilyn
ABSTRACT: This study investigates the impediments that Australian, female, independent filmmakers face in bringing female-centred stories onto the screen. In 2016, the federal screen funding agency Screen Australia launched Gender Matters to better understand the many barriers facing women filmmakers and create opportunities for female screen creatives to gain equity in the screen industries. But how have this impacted and improved conditions for female filmmakers? The authors of this current study are female screenwriters, directors and producers who have experienced and witnessed the many difficulties women face in the Australian screen industry. The article comprises case studies of recent, successful, female, independent feature filmmakers, the AACTA Award nominated creators of Strange Colours, The Second and Hot Mess. The research explores emergent themes and recommendations based on interviews with the filmmakers. They observe that while some impediments in the low budget, independent sector continue, others have subsided and a considerable number of promising developments are emerging. Screen Australia's Gender Matters and other initiatives by State-based screen agencies have encouraged this progress, but changes in the global socio-cultural discourse have also been influential.